Sikap Bahasa Pramuniaga Yang Berbahasa Ibu Bahasa Aceh terhadap Bahasa Aceh di Banda Aceh - Ella Maulida; Rostina Taib; Herman R Herman R (JIM Pendididikan Bahasa dan Sastra Indonesia, 2020)
This study is entitled “Attitudes of Language Servants who Speak the Mother Language of Aceh in Banda Aceh”. the problem in this research is how is the attitude of the language of the saleswoman who spoke the mother tongue of Aceh to the language? This study aims to describe the saleswoman who speaks the mother tongue of Aceh towards the Aceh language. This research is the saleswoman in Banda Aceh. The method used in this research is descriptive quatitative method. The population of all saleswoman who spoke the  mother tongue of Aceh against the Acehnese language. The research data were obtained from the answer to the questionnaire respondents who were respondents. The questionnaire was prepared based on a Likert Scale with five levels, namely strongly agree (SS), agree (S), doubt (RR), disagree (TS), and strongly agree (STS). The results showed that the attitude of the saleswoman’s language who spoke the mother tongue of Aceh towards the Acehnese language was positive and negative. Positive language attitude consists of loyalty which is in the category of getting quite a percentage of 53%, pride in the good category gets a precentage of 71% and awareness is ini the category of getting a precentage og 66%. A negative attitude towards the Acehnese language cansists of the lack of passion or encouragement to maintain the independence of the language, which is in the category of getting a percentage of 56%. The lack of awareness of language norms is in the category of enough to get a percentage of 69%. and do not have a sense of pride in the language is in the category of enough to get a precentage og 61%. Thus the attitude of the saleswoman in Banda Aceh towards the Acehnese language was included in the positive category